2016
DOI: 10.1016/j.peva.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of influence power for information security decisions

Abstract: Users of computing systems and devices frequently make decisions related to information security, e. g., when choosing a password, deciding whether to log into an unfamiliar wireless network. Employers or other stakeholders may have a preference for certain outcomes, without being able to or having a desire to enforce a particular decision. In such situations, systems may build in design nudges to influence the decision making, e. g., by highlighting the employer's preferred solution. In this paper we model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…They reported that nudges could be effective, but that personal differences also played a role in security decisions. Yevseyeva et al (2016) also experimented with the use of influential techniques to steer people towards the most secure Wi-Fi option. Among other insights, they found that adding a padlock symbol had the highest impact, but also that the influence decreased as the number of options increased, and that different clusters of decision-makers existed.…”
Section: Related Workmentioning
confidence: 99%
“…They reported that nudges could be effective, but that personal differences also played a role in security decisions. Yevseyeva et al (2016) also experimented with the use of influential techniques to steer people towards the most secure Wi-Fi option. Among other insights, they found that adding a padlock symbol had the highest impact, but also that the influence decreased as the number of options increased, and that different clusters of decision-makers existed.…”
Section: Related Workmentioning
confidence: 99%
“…A security-related nudge study [54] successfully nudged users towards a more secure WiFi by using colour and menu order. This finding was confirmed by [55]. Privacy researchers have deployed nudges with some success [56,57,58] making people more aware of privacy invasions.…”
Section: What About the Information Security Context?mentioning
confidence: 76%
“…Once the data has been aligned, the resultant data will be sent to the Correlation Power Analysis (CPA) [55] attack. The CPA attack is utilised to recover the secret key used by the AES-128 algorithm with the EM emissions as input data.…”
mentioning
confidence: 99%
“…Developer-centered security is an emerging research area focused on how to get developers to build more secure systems from the start [44,57]. While the traditional focus of cybersecurity research has been on developing new technologies and systems, in recent years, this is shifting to understanding the software engineer and how they are supported in creating secure products [53,23].…”
Section: Related Workmentioning
confidence: 99%